1983
DOI: 10.1159/000214822
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Immunological Characterization of Plasminogen Activators in Human Prostate Tissue

Abstract: In tissue sections of human hyperplastic as well as carcinomatous prostate glands ñbrinolytic activity could be attributed to collecting ducts and vessel walls. Inhibition studies with antibodies directed against human urokinase (u-PA) or tissue plasminogen activator (t-PA) revealed the presence of a plasminogen activator completely inhibitable by anti-t-PA IgG in the vessel walls, while in collecting ducts the plasminogen activator activity was inhibited by anti-u-PA IgG to only 80% and by anti-t-PA IgG to ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…PAA of the seminal plasma was affected immediately and the PA1 with a delay after the increase of testosterone in the blood through apparently an effect on PAA or PA1 in epithelial cells of cauda epididymidis, vas deferens, seminal vesicles and prostate gland. PAA (t-PA or u-PA) has been demonstrated in all these areas of the male genital system (Burleigh et al, 1980;Kirchheimer & Binder, 1983;Larsson et a1.,1984;Rennie et al, 1984;Huarte et al, 1987;Reese et al, 1988;Martikainen et al, 1989;Andreasen et al, 1990;Wilson et al, 1990). It has been also reported that testosterone can increase significantly the secretion of PA in organ culture of'rat ventral prostate (Martikainen et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…PAA of the seminal plasma was affected immediately and the PA1 with a delay after the increase of testosterone in the blood through apparently an effect on PAA or PA1 in epithelial cells of cauda epididymidis, vas deferens, seminal vesicles and prostate gland. PAA (t-PA or u-PA) has been demonstrated in all these areas of the male genital system (Burleigh et al, 1980;Kirchheimer & Binder, 1983;Larsson et a1.,1984;Rennie et al, 1984;Huarte et al, 1987;Reese et al, 1988;Martikainen et al, 1989;Andreasen et al, 1990;Wilson et al, 1990). It has been also reported that testosterone can increase significantly the secretion of PA in organ culture of'rat ventral prostate (Martikainen et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…Plasminogen activators and plasminogen activator inhibitors in seminal plasma should predominantly be the result of their synthesis from epithelial cells of cauda epididymis, vas deferens, seminal vesicles, and prostate gland. At least PAA (t-PA or u-PA) has been demonstrated in all these areas of the male genital system (Burleigh et al, 1980;Kirchheimer & Binder, 1983;Larsson et al, 1984;Rennie et al, 1984;Huarte et al, 1987;Reese et al, 1988;Martikainen et al, 1989;Andreasen et al, 1990;Wilson et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to prostate cancer, one of the most frequently occurring malignancies in elderly men, most data exist on plasminogen activators specifically on uPA [52][53][54][55] and malignancy of the tumor, but only scarcely data on PAI-1 [56][57][58].…”
Section: Urinary Tractmentioning
confidence: 99%